Racial Socialization, Racial Identity, and Academic Attitudes Among African American Adolescents: Examining the Moderating Influence of Parent–Adolescent Communication - Tang, Sandra (J Youth Adolesc, 2015)
A significant gap remains in our understanding of the conditions under which parents’ racial socialization has consequences for adolescents’ functioning. The present study used longitudinal data to examine whether the frequency of communication between African American parents and adolescents (N = 504; 49 % female) moderates the association between parent reports of racial socialization (i.e., cultural socialization and preparation for bias) at 8th grade and adolescent reports of racial identity (perceived structural discrimination, negative public regard, success-oriented centrality) at 11th grade, and in turn, academic attitudes and perceptions. Parents’ racial socialization practices were significant predictors of multiple aspects of adolescents’ racial identity in families with high levels of communication, but they did not predict any aspects of adolescents’ racial identity in families with low levels of communication. Results highlight the importance of including family processes when examining the relations between parents’ racial socialization and adolescents’ racial identity and academic attitudes and perceptions.